2021
DOI: 10.1002/jlb.5a1019-522rr
|View full text |Cite
|
Sign up to set email alerts
|

Innate lymphoid cell recovery and occurrence of GvHD after hematopoietic stem cell transplantation

Christelle Piperoglou,
Guillaume Larid,
Blandine Vallentin
et al.

Abstract: Lymphocytes are essential for microbial immunity, tumor surveillance, and tissue homeostasis. However, the in vivo development and function of helper‐like innate lymphoid cells (ILCs) in humans remain much less well understood than those of T, B, and NK cells. We monitored hematopoietic stem cell transplantation (HSCT) to determine the kinetics of ILC development in both children and adults. It was found that, unlike NK cells, helper‐like ILCs recovered slowly, mirroring the pattern observed for T cells, with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 58 publications
(74 reference statements)
2
5
0
Order By: Relevance
“…First, we confirmed in this independent cohort of 36 allogeneic HCT patients that the percentage of ILCs in the blood of allogeneic HCT patients was significantly reduced compared with blood of healthy individuals, and that patients with a relatively higher frequency of ILCs immediately before allogeneic HCT seemed significantly less likely to develop acute GvHD than patients with a relatively lower frequency of ILCs before allogeneic HCT. These results verify previous findings of our group and others that ILC reconstitution in blood after remission-induction chemotherapy is slow, that reconstitution of ILC3s is generally faster than that of ILC2s and that having more ILCs before allogeneic HCT is likely protective for acute GvHD [16,25]. Although the group of healthy donors included in our study was relatively small (n = 5), they closely match the findings in healthy donors in our previous study [16].…”
Section: Discussionsupporting
confidence: 92%
“…First, we confirmed in this independent cohort of 36 allogeneic HCT patients that the percentage of ILCs in the blood of allogeneic HCT patients was significantly reduced compared with blood of healthy individuals, and that patients with a relatively higher frequency of ILCs immediately before allogeneic HCT seemed significantly less likely to develop acute GvHD than patients with a relatively lower frequency of ILCs before allogeneic HCT. These results verify previous findings of our group and others that ILC reconstitution in blood after remission-induction chemotherapy is slow, that reconstitution of ILC3s is generally faster than that of ILC2s and that having more ILCs before allogeneic HCT is likely protective for acute GvHD [16,25]. Although the group of healthy donors included in our study was relatively small (n = 5), they closely match the findings in healthy donors in our previous study [16].…”
Section: Discussionsupporting
confidence: 92%
“…However, it increased after the transplant and took one year to come back to the normal range in recipients with the non-GVHD group, whereas in the children it took only 6 months. They have also found a similar association with the homing markers as above mentioned [ 43 , 44 ]. Both studies suggested that ILC1 population reconstitution was not affected by graft origin or by the amount of CD34 stem cells in the graft.…”
Section: Ilc1 and Stem Cellssupporting
confidence: 73%
“…In 2021. Piperoglou et al studied the ILC population reconstitution after HSCT in adult and young patients [ 44 ]. They found that ILC1 levels in adult patients before the HSCT were the same as that in the healthy controls [ 44 ].…”
Section: Ilc1 and Stem Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…Adding to this, ILCs typically function in cellular networks to influence the outcome of a given immune response. To properly understand their function and tease out any redundancy, more systemsbased approaches are needed, particularly in humans (295,372,373).…”
Section: Discussionmentioning
confidence: 99%